Performance evaluation of cluster based cooperative cognitive radio network / M. Moradkhani and Z. Zalani - Moradkhani, M.; Zalani, Z. (UiTM Press, 2016)
Cognitive radio is regarded as one of the transformational technologies that play a fundamental role in establishment and development of next generation wireless networks. Clustering based cognitive radio networks can reduce the energy consumption and increase the spectrum sensing accuracy. In this paper, we investigate the performance of a cognitive radio network with a clustering architecture for cooperative spectrum sensing. The network efficiency is evaluated in terms of throughput and energy consumption, under fading channel conditions. Simulation results show significant improvement of energy efficiency compared to the conventional non-clustering method by ensuring allowable interference with primary users.